Outcome of R-CHOP or CHOP Regimen for Germinal Center and Nongerminal Center Subtypes of Diffuse Large B-Cell Lymphoma of Chinese Patients. (31st October 2012) - Huang, Ying; Ye, Sheng; Cao, Yabing; Li, Zhiming; Huang, Jiajia; Huang, He; Cai, Muyan; Luo, Rongzhen; Lin, Tongyu
Abstract : Diffuse large B-cell lymphoma (DLBCL) can be molecularly subtyped as either germinal center B-cell (GCB) or non-GCB. The role of rituximab(R) in these two groups remains unclear. We studied 204 patients with de novo DLBCL (107 treated with first-line CHOP; 97 treated with first-line R-CHOP), patients being stratified into GCB and non-GCB on the basis of BCL-6, CD10, and MUM1 protein expression. The relationships between clinical characteristics, survival data, and immunophenotype (IHC) were studied. The 5-year overall survival (OS) in the CHOP and R-CHOP groups was 50.4% and 66.6% (P = 0.031 ), respectively. GCB patients had a better 5-year OS than non-GCB patients whether treated with CHOP or not (65.0% versus 40.9%;P = 0.011 ). In contrast, there is no difference in the 5-year OS for the GCB and non-GCB with R-CHOP (76.5% versus 61.3%;P = 0.141 ). In non-GCB subtype, additional rituximab improved survival better than CHOP (61.3% versus 40.9%;P = 0.0303 ). These results indicated that addition of rituximab to standard chemotherapy eliminates the prognostic value of IHC-defined GCB and non-GCB phenotypes in DLBCL by improving the prognostic value of non-GCB subtype of DLBCL.